La ética de Kant como fundamento para una educación moral en nuestros días - Sarango Zárate, Jorge Enrique (2024)
The purpose of this paper is to analyze the proposal of Kant’s ethics and see how it is possible to educate people in the moral field based on this theory. Therefore, the distinctions of actions are made explicit by duty and according to duty, where the former allows the adoption of universal moral laws in order to guide human action by implying that the subject should see people as an end in itself, in a dignified manner and not see them as means; while the second, contemplates performing moral actions for a purpose other than duty itself. Therefore, unveiling the ethics of Kant we will show that in our days it is vital for moral education to inculcate in young people a Kantian moral perspective because from such a theory we can derive perfectly the moral actions that are needed in our society. It is not intended to derive from moral actions the importance of Kantian ethics because we would be contravening his proposal, but we can draw examples, as Kant himself did in his time. In our case, it will be done with the aim of demonstrating the importance that Kant’s ethics can have for a moral education in our days.